2006
DOI: 10.1007/s10695-005-0560-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel gill-specific calpain from rainbow trout (Oncorhynchus mykiss)

Abstract: Calpains are calcium-dependent neutral proteases responsible for many cellular functions. The two forms of calpain ubiquitously expressed in mammalian tissues are known as mu-calpain and m-calpain. We report here the identification of a novel calpain that is similar to but distinct from the mu- and m-calpains in rainbow trout. The cDNA of the novel gene is 2623 bp in length with a single open reading frame. The predicted protein (676 amino acids) contains the conserved calpain characteristic domains that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this report, we described the isolation of a tissue-specific calpain cDNA out of a catfish barbell epithelium cDNA library. Calpains have been reported in other non-mammalian species including CAPN1 & CAPN2 in carp muscle [25], those in trout muscle [26] and gill-specific calpain of rainbow trout [27]. The calpain reported on here encodes a 687 amino acid protein with a predicted molecular weight of 78,345 Da.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this report, we described the isolation of a tissue-specific calpain cDNA out of a catfish barbell epithelium cDNA library. Calpains have been reported in other non-mammalian species including CAPN1 & CAPN2 in carp muscle [25], those in trout muscle [26] and gill-specific calpain of rainbow trout [27]. The calpain reported on here encodes a 687 amino acid protein with a predicted molecular weight of 78,345 Da.…”
Section: Discussionmentioning
confidence: 68%
“…Salem et al showed that rainbow trout gill-specific calpain, closely related to calpain 9, was not expressed in the small intestine. Different detecting probes used in the northern blot analysis may explain this difference [27].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, several of these genes are known to be specifically or predominantly expressed in the gills (Table 6). Included in the gill-specific genes is a new calpain, which was reported to be expressed in the trout gill by Salem et al (2006). Additionally, we identified several ion transporters such as Na/K-ATPaseα1a, which was previously shown to be overexpressed in gill tissue by Richards et al (Richards et al, 2003).…”
Section: The Identification Of Genes That Are Preferentially Expressementioning
confidence: 82%